Retirement Saving Behavior of Employees of the Government Housing Bank, Head Office: Retirement Saving Behavior of Employees of the Government Housing Bank, Head Office - Saenghiranphonsiri, Wipabhorn; Phetsatit, Pongsak; Sirivisitkul, Sanit (RATANABUTH JOURNAL, 2024)
The financial planning of most Thais is still insufficient to support life after retirement. As a result, the risk of "failing to retire" is high, meaning retirees may not have enough money to live on. It is crucial to have a significant amount of savings in order to maintain a reasonable quality of life during retirement. The objectives of this research were: 1) to study the level of retirement saving behavior among employees of the Government Housing Bank, 2) to compare the retirement saving behavior of these employees, categorized by personal factors. The sample group used in this research consists of 310 employees from the Government Housing Bank’s headquarters. The data collection tool was a questionnaire. The statistics used in this research include frequency, percentage, mean, standard deviation, t-test, and F-test. The research findings revealed that the overall level of retirement saving behavior among employees of the Government Housing Bank was high. When considering each aspect, it was found that the highest mean score was in the area of retirement saving methods, while the lowest was in retirement saving planning and allocation. A comparison of retirement saving behavior, categorized by personal factors, showed that employees with different monthly expenses had significantly different retirement saving behaviors at the 0.05 level of statistical significance. No differences were found for other variables.